Analisis Tingkat Ramah Lingkungan pada Alat Tangkap Jaring Insang Dasar (Bottom Gill Net) di Pantai Depok D.I Yogyakarta. - Achmad Fahran Syifannur (Manfish: Jurnal Ilmiah Perikanan dan Peternakan, 2025)
Capture fisheries are an important economic sector in the coastal area of ​​Depok Beach, Yogyakarta Special Region. Fishing activities in this area use various fishing gear, one of which is the bottom gill net. However, the use of this fishing gear can have negative impacts on the aquatic environment and marine ecosystem, such as the decline in the population of white pomfret and ribbonhead fish, which are the main catch. This study aims to analyze the level of environmental friendliness of the use of bottom gill nets in Depok Beach using a descriptive quantitative approach. The methods used in this study include direct surveys of fishermen, observation of fishing operations, and analysis of catch results. Data were collected through a questionnaire containing 9 indicators compiled by the FAO, which cover aspects of gear selectivity, impact on aquatic habitats, fisherman safety, catch quality, and social acceptance of the fishing gear. The results showed that bottom gill nets had the lowest level of selectivity with a score of 1.13, indicating that this tool is less selective in selecting the types of fish caught. However, the indicator regarding consumer safety received the highest score of 4.00. Overall, the test results show that the use of bottom gill nets at Depok Beach has an environmental friendliness score of 27.06, which indicates that this fishing gear is classified as environmentally friendly even though it needs improvement in terms of selectivity.